Usaha “Ngentang”sebagai makanan favorit bagi konsumen kekinian dengan rasa yang unik - Prabandari, Wijayanti Dewi; Darsiah, Anis; Yuriko, Yuriko (Jurnal Pemberdayaan Pariwisata, 2025)
This Community Service activity was motivated by the low level of involvement of students and youth in high-value local culinary-based entrepreneurial activities. The main objective of this program is to empower the community, particularly students and youth around the Trisakti Institute of Tourism, through skills training and entrepreneurship education so that they can independently improve their income and quality of life. The implementation method consisted of three main stages: planning, socialization, and execution. The training covered materials on entrepreneurial concepts, innovation in potato-based food products, digital marketing strategies, and basic financial management for micro businesses. The results of the activity showed a significant increase in participants’ knowledge and skills, as reflected in the pre-test and post-test outcomes, as well as the successful production and marketing of the culinary product "Ngentang". During the three-month trial period, 116 product units were sold with a total revenue of IDR 2,088,000. This program effectively fostered entrepreneurial spirit, enhanced practical skills, and encouraged participants to continue developing sustainable business ventures. Keywords:  entrepreneurship, culinary innovation, digital marketing